Study on the Comfort Properties of Knitted Fabrics Produced from Conventional and Sustainable Cotton and Polyester Fibres - Arzu Marmarali; Mehmet Sevgi (Tekstilec, 2023)
Recently, the production of organic fibres and the recycling of textile waste have become essential global issues due to the decrease in non-renewable resources and the increase in disposal costs. The aim of this work was to identify changes in the properties of single jersey knitwear produced from conventional and sustainable fibres after 20 washes. The samples were knitted from different conventional and sustainable yarns. The selected conventional fibres were 100% cotton, 50% cotton-50% polyester and 100% polyester, while the sustainable fibres were 100% better cotton, 100% recycled polyester, and 50% organic cotton-50% recycled polyester. Measurements were taken before and after 20 washes according to the relevant standards. It was found that fabric produced from 100% recycled polyester is suitable for active sportswear due to its high air permeability, and resistance to heat and water vapor. In addition, the fabric with 50% organic cotton-50% recycled polyester fibres was more suitable for cold environmental conditions due to its lowest water vapor resistance, good air permeability and high thermal resistance.